(untitled) (Fiep Bulletin - online, 2014)
The objective of this study is to verify the acute effect on the decrease of muscular force endurance after the execution of Proprioceptive Neuromuscular Facilitation exercises (PNF). Methodology: 20 men, 23,1±5,2 of age who underwent 14 weeks of training participated in the study. The 1RM was used to verify the maximum load in the bench press exercise where a value of 75% was calculated after the exercise. After the test, the subjects were divided into two groups: Experimental Group (EG) and Control Group (CG). The EG executed the maximum number of repetitions with 75% of the maximum load obtained in the 1RM test and the PNF exercise was executed after an interval of 10min, followed by a new series with the same load and a new interval of 10min was given before the third trial. The CG executed the same procedure, except for the execution of the PNF exercise. Results: A mean of 10,6±0,9 repetitions in the first series, 9,0±0,9 in the second series and 8,8±1,0 in the third series was observed in the EG, showing a significant difference (p=0,0001<0,05). The (CG) reached a mean of 12,5±1,2 repetitions in the first series, 11,6±1,0 in the second series and 10,8±0,8 in the third series, showing no significant difference (p=0,0574>0,05); Conclusion: when the PNF exercises are executed before strength training, this causes a decrease in strength endurance.